La fragilité et le rôle passif de la femme (Journal of the College of Basic Education, 2023)
Marguerite Duras: a brilliant name in the novel world. ...the novelist who didn't stop writing till the end of her days, and more, her productions and creativity exceeded to theatres and movies as a writer and a director. Duras has established a modern european cinema since her novels were represented in this domain. The Lover (1984), which received the Goncours award; this novel tells the story of this novelist, her life as a teenage and young girl. It is a story of a girl who lives with her family in Vietnam during the French occupation. A French family that lives in the midlist of an Asian society... A fifteen years old girl who sees her premature growing and tries to look for the independence of her feelings in a dismembered family and finds her feminine with a Chinese rich young man . She lives then with him physically and emotionally. The Lover demonstrates how much fragile a woman can get in such situations and her strength in other ones. The Lover is the true tragedy of Duras with a mother who doesn't love her and prefers her old brother. The Lover,that was made a movie, transformed Duras not only into one of the new novel pioneers, but also one of love ladies